Polymorphisms of MTHFR Associated with Higher Relapse/Death Ratio and Delayed Weekly MTX Administration in Pediatric Lymphoid Malignancies. (10th December 2013) - Fukushima, Hiroko; Fukushima, Takashi; Sakai, Aiko; Suzuki, Ryoko; Nakajima-Yamaguchi, Ryoko; Kobayashi, Chie; Iwabuchi, Atsushi; Saito, Makoto; Yoshimi, Ai; Nakao, Tomohei; Kato, Keisuke; Tsuchida, Masahiro; et al.
Abstract : Backgrounds . Outcome of childhood malignancy has been improved mostly due to the advances in diagnostic techniques and treatment strategies. While methotrexate (MTX) related polymorphisms have been under investigation in childhood malignancies, many controversial results have been offered. Objectives . To evaluate associations of polymorphisms related MTX metabolisms and clinical course in childhood lymphoid malignancies. Method . Eighty-two acute lymphoblastic leukemia and 21 non-Hodgkin's lymphoma children were enrolled in this study. Four single nucleotide polymorphisms in 2 genes ( MTHFR (rs1801133/c.677C>T/p.Ala222Val and rs1801131/c.1298A>C/p.Glu429Ala) and SLCO1B1 (rs4149056/c.521T>C/p.V174A and rs11045879/c.1865+4846T>C)) were genotyped by Taqman PCR method or direct sequencing. Clinical courses were reviewed retrospectively. Results . No patient who had the AC/CC genotype of rs1801131 ( MTHFR ) had relapsed or died, in which distribution was statistically different among the AA genotype of rs1801131 (P = 0.004 ). Polymorphisms of SLCO1B1 (rs11045879 and rs4149056) were not correlated with MTX concentrations, adverse events, or disease outcome. Conclusions . Polymorphisms of MTHFR (rs1801131) could be the plausive candidate for prognostic predictor in childhood lymphoid malignancies.